2020
DOI: 10.1186/s12913-020-05460-7
|View full text |Cite
|
Sign up to set email alerts
|

Causes of maternal deaths and delays in care: comparison between routine maternal death surveillance and response system and an obstetrician expert panel in Tanzania

Abstract: Background: To reduce maternal mortality Tanzania introduced Maternal Death Surveillance and Response (MDSR) system in 2015 as recommended by World Health Organization (WHO). All health facilities are to notify and review all maternal deaths inorder to recommend quality improvement actions to reduce deaths in future. The system relies on consistent and correct categorization of causes of maternal deaths and three phases of delays. To assess its adequacy we compared the routine MDSR categorization of causes of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
1
36
0
2
Order By: Relevance
“… 11 15 22–24 Literature shows that improving knowledge and skills of providers and integrating MDSR with other systems and stakeholders will improve the efficiency of the system in identification, notification and review of deaths. 14 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 15 22–24 Literature shows that improving knowledge and skills of providers and integrating MDSR with other systems and stakeholders will improve the efficiency of the system in identification, notification and review of deaths. 14 25 …”
Section: Discussionmentioning
confidence: 99%
“…Two studies done recently on Tanzanian MDSR system reported strengths and challenges in reporting causes of death, delays in care provision and comprehensiveness of documents. 14 15 We also aimed to explore reasons for the shortcomings identified by these studies from providers and managers perspectives. Therefore, study aims to analyse health providers’ and managers’ perceptions and experiences of the implementation of the MDSR system in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that records’ abstraction resulted in providing only 54% of the standard information required. Furthermore, a study on identification of causes and three delays in the MDSR system in Tanzania revealed that when using narrative summaries, the providers failed to identify most of the gaps in care that contributed to that death [ 27 ]. This also impacted the action plans from such reviews.…”
Section: Discussionmentioning
confidence: 99%
“…(14).They reported that chart abstraction resulted into only 54% of the standard information required. Furthermore a study on identi cation of causes and three delays in MDSR system in Tanzania revealed that using narrative summaries, the providers failed to identify most of the gaps in care that contributed to death (27). This also impacted the action plans from such reviews.…”
Section: Comprehensiveness Of the Narrative Summaries And Action Plansmentioning
confidence: 99%